Ekosufisme Majelis Zikir Kraton Habib Muhamad Dardanylla Shahab Pekalongan - Laila, Nur (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2018)
This article investigates the Majlis Dhikr Kraton Pekalongan City’s concern on the ecosystem environment. The data are derived from qualitative methods by means of interviews and observations. This article presents two conclusions. First, the Majlis of Dhikr Kraton Pekalongan City is aware that the environment is created by Allah, which is dedicated for humans and their fellow beings. Secondly, the Majlis Dhikr Kraton of Pekalongan City has made important steps in its attempt of conserving, either in the form of handling or preventing the environment and ecosystem safety. Environmental damage is handled by processing textile wastewater, processing solid waste (garbage), repairing land through agriculture and plantation sectors, improving land through the fisheries sector, and cleaning up air pollution. The precautionary measures are implemented in the form of making infiltration wells and biopori holes in addition to socialization to the community.